2010
DOI: 10.1097/aog.0b013e3181cb59da
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Alcohol-Induced Learning Deficits in the Young Adult in a Model of Fetal Alcohol Syndrome

Abstract: Alcohol-induced learning deficit was reversed and expression of NR2A and NR2B was restored in the hippocampus and cortex of young adult mice treated with D-NAPVSIPQ and D-SALLRSIPA. Given the role of NMDA receptors in learning, this may explain in part the mechanism of prevention of alcohol-induced learning deficits by D-NAPVSIPQ and D-SALLRSIPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
2
18
1
1
Order By: Relevance
“…Mice were then gavaged with two neuroprotective peptides (D-NAP + D-SAL) between postnatal days 67 and 76 and their performance in the Morris water maze task was assessed. In contrast to recent results (Incerti et al, 2010), injection of ethanol during gestational day 8 did not produce significant alterations in spatial learning and memory. In contrast, injection during postnatal day 7 did produce significant alterations in the Morris water maze test.…”
Section: Fast Data Presentationscontrasting
confidence: 99%
“…Mice were then gavaged with two neuroprotective peptides (D-NAP + D-SAL) between postnatal days 67 and 76 and their performance in the Morris water maze task was assessed. In contrast to recent results (Incerti et al, 2010), injection of ethanol during gestational day 8 did not produce significant alterations in spatial learning and memory. In contrast, injection during postnatal day 7 did produce significant alterations in the Morris water maze test.…”
Section: Fast Data Presentationscontrasting
confidence: 99%
“…Neurodegeneration can be observed in these cell populations even following single ethanol exposure periods (Dikranian et al, 2005;(Goodlett and Eilers, 1997; Marcussen et al, 1994), such as those used in the present study. Moreover, developmental alcohol exposure can influence the structure and function of surviving cells, reducing myelin (Zoeller et al, 1994), reducing synaptic connections (Klintsova et al, 2002), altering receptor and ion channel function (Gruol and Parsons, 1996; Incerti et al, 2010; Servais et al, 2007), and impairing plasticity (Servais et al, 2007). It is possible that any of these alcohol effects could contribute to motor deficits and/or be affected by memantine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of animal research suggest the promise of various prenatal and neonatal interventions, including prenatal and postnatal treatment with neuroprotective Child Psychiatry Hum Dev peptides [127] and various nutrients [128][129][130][131][132]. Other research has demonstrated positive effects of neonatal handling, postnatal environment enrichment, and rehabilitative training on rats and mice with perinatal alcohol exposure [133].…”
Section: Treatmentmentioning
confidence: 96%